Rational and Intuitive Brains in Islamic Education: Analysis of Al Ma'un Theology in the Neurosains Perspective - Nurjanah Wijayanti; Suyadi (Tarbiyah Departement collaboration with AMCA, 2020)
The main problem of this research is the